SYSTEM AND ELEMENTS OF DA'WAH THEORY DEVELOPMENT - Liya Nikmah Jazhila (Program Studi Komunikasi dan Penyiaran Islam Pascasarjana UIN KHAS Jember, 2022)
The term da'wah has long been used and spoken widely among the public. It originates from the command of Allah, found in both the Qur’an and the hadiths of the Prophet Muhammad. Commonly paired with the word